DIETARY SELENIUM YEAST SUPPLEMENTATION IMPROVED SOME VILLI MORPHOLOGICAL CHARACTERISTICS IN DUODENUM AND JEJUNUM OF YOUNG GOATS - Z. Ahmed; M. Malhi; S. A. Soomro; J. A. Gandahi; A. Arijo; B. Bhutto; T. A. Qureshi (Journal of Animal and Plant Sciences, 2016)
The present study evaluated the effects of Selenium Yeast, (SY) on villi morphology in small intestine of young goats. Ten cross-bred goats of age 110-130 days and weighing 9.93 -10.71 kg, at the commencement of experiment, were used in present study. Animals were fed basal diet consisting of hay and concentrate. The concentrate (2 % BW) was provided into two equal portions at 0800 and 1700 h daily and the hay was fed at ad libitum. Water was provided at ad libitum. Animals were allocated into two dietary groups, consisting of basal diet (CON), or basal diet with Selenium Yeast, 0.3 mg/kg feed (SY). The results showed that the duodenal and jejunal masses (grams per kilogram empty body weight, g/kg EBW) in SY (3.2 ± 0.09 and 6.69 ± 0.17) increased significantly (P < 0.05) than in CON (2.88 ± 0.09 and 6.13 ± 0.26). Dietary treatments did not alter (P > 0.05) the lengths of intestine, duodenum, jejunum and ileum compared to CON. Mucosal weight (%) was higher (P < 0.05) in the duodenum (76.75 ± 0.68) and jejunum (76.3 ± 0.19) of SY goats than that of CON (73.53 ± 0.82 and 72.99 ± 0.85). In duodenum, the villus height (µm) increased (P < 0.05) in SY (559.98 ± 23.22) as compared to CON (468.32 ± 31.41). In jejunum, villus height and width increased (P < 0.05) in SY (578.06 ± 15.68 and 77.30 ± 2.56) compared to control (437.88 ± 29.12 and 63.84 ± 3.22). The improvement in villi dimensions (length and width) led to increase (P < 0.05) in villus surface area by 36.2 and 58.81 % in duodenum and jejunum of SY fed goats compared to that of CON. Dietary treatments did not alter villi morphology in ileum. It can be concluded from the present study that dietary SY supplementation produced positive effects on some villi morphological characteristics in both duodenum and jejunum of goats.
Keywords: Selenium Yeast; Intestine; Goats; villi; Organic selenium